2000
DOI: 10.1002/1521-3773(20001103)39:21<3874::aid-anie3874>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thymine Glycol Containing Oligonucleotides from a Building Block with the Oxidized Base

Abstract: One major type of oxidative base damage in DNA is the formation of thymine glycol (shown as part of an oligonucleotide in the picture), which blocks DNA replication. A nucleoside phosphoramidite with this damaged base was synthesized and incorporated into oligonucleotides. This method enables facile preparation of damaged DNA without limitations in chain length, sequence, and yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…DNA oligonucleotides were purified by denaturing polyacrylamide gel electrophoresis (DPAGE). Five pmol of each primer was 5Ј-end-labeled with T4 polynucleotide kinase (Invitrogen) in the presence of [␥- 32 P]ATP, and the unincorporated radiolabel was removed using a Sephadex G-25 spin column equilibrated with STE (100 mM NaCl, 10 mM Tris, pH 8.0, 1 mM Na 2 EDTA). Primers were annealed to template strands in a stoichiometric ratio of 1:1.5 (primer-template) by heating (90°C, 5 min, 1ϫ STE buffer) and cooling on the bench top (15 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA oligonucleotides were purified by denaturing polyacrylamide gel electrophoresis (DPAGE). Five pmol of each primer was 5Ј-end-labeled with T4 polynucleotide kinase (Invitrogen) in the presence of [␥- 32 P]ATP, and the unincorporated radiolabel was removed using a Sephadex G-25 spin column equilibrated with STE (100 mM NaCl, 10 mM Tris, pH 8.0, 1 mM Na 2 EDTA). Primers were annealed to template strands in a stoichiometric ratio of 1:1.5 (primer-template) by heating (90°C, 5 min, 1ϫ STE buffer) and cooling on the bench top (15 min).…”
Section: Methodsmentioning
confidence: 99%
“…Both procedures result in a mixture of the four possible stereoisomers of Tg in different relative proportions (Fig. 1B) (32,33). We show by both qualitative and quantitative steady-state kinetic analysis that pol supports TLS across both of these substrates.…”
mentioning
confidence: 99%
“…11-mers with the same sequence, were used for two reasons. One reason was that a tetramer could not be the substrate for uracil DNA glycosylase in the preparation of the AP site-containing oligonucleotide, and the other reason was that relatively long sequences were favorable at the deprotection step in our synthesis of the thymine glycol-containing oligomers (26). A dinucleoside monophosphate and a 30-mer containing the (6-4) photoproduct were used for the NMR experiments and the biochemical assays, respectively, as described in the following sections.…”
Section: Design and Preparation Of Oligonucleotides-mentioning
confidence: 99%
“…In this regard, Iwai (33,34) described the synthesis of a building block of thymidine glycol where the nucleobase hydroxyl group(s) were protected with tert-butyldimethylsilyl (TBDMS) group. Very recently, Cadet et al (35) reported the synthesis of a Tg building block where the nucleobase hydroxyl group(s) was protected with a base-labile levulinyl functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Cadet et al (35) reported the synthesis of a Tg building block where the nucleobase hydroxyl group(s) was protected with a base-labile levulinyl functionality. On the other hand, the deprotection of ODNs synthesized from the commercially available building block of 8-oxodG requires prolonged treatment with concentrated ammonium hydroxide; during such treatment, thymidine glycol, however, was shown to be significantly degraded (33). Therefore, dual insertion of 8-oxodG and thymidine glycol necessitates alternative synthetic strategies.…”
Section: Introductionmentioning
confidence: 99%